Autonomic Function in Patients With Parkinson’s Disease: From Rest to Exercise - Sabino-Carvalho, Jeann L.; Fisher, James P.; Vianna, Lauro C. (Frontiers in Physiology, 2021)
Parkinson’s disease (PD) is a common neurodegenerative disorder classically characterized by symptoms of motor impairment (e.g., tremor, rigidity), but also presenting with important non-motor impairments. There is evidence for the reduced activity of both the parasympathetic and sympathetic limbs of the autonomic nervous system at rest in PD. Moreover, inappropriate autonomic adjustments accompany exercise, which can lead to inadequate hemodynamic responses, the failure to match the metabolic demands of working skeletal muscle, and exercise intolerance. The underlying mechanisms remain unclear, but relevant alterations in several discrete central regions (e.g., dorsal motor nucleus of the vagus nerve, intermediolateral cell column) have been identified. Herein, we critically evaluate the clinically significant and complex associations between autonomic dysfunction, fatigue, and exercise capacity in PD.